A Brief Survey on Impact of Flood on Children, Water Sanitation and Hygiene in Kashmir Valley - Irshad Ahmad Yatoo; Prof. Bhakti Chourey; Khursheed Aalum (International Journal of Engineering and Management Research, 2018)
Considerable rainfall raises the water level. When the water level is higher than the conduit bank, the water diverts out from the stream, there will surge. Surges are caused by atmosphere ponders and events that pass on more precipitation to a waste bowl that can be immediately absorbed or secured inside the bowl. Surges can be caused by typical, natural or anthropogenic factors. There are a couple of purposes behind surges and change from region to area. Flood is coming to fruition in view of unprecedented geophysical event to make an astounding danger to human life and property. Surge occurring in thickly populated locale can do most extraordinary mischief to life and property. Country practices and deforestation have altogether changed the condition in whole stream bowls. Passing, disease, harm, expulsion of people and fiscal hardship are the standard consequences of surge. So the purpose of this examination work is to research the effect of flooding on children, water sanitation and cleanliness.